D-amino acid/gentamicin loaded zwitterionic hydrogel coatings with optimized mechanical stability and biofilm inhibition capabilities - Yang, Jingzhi; Ran, Yami; Zhao, Junsen; Xing, Taiwei; Hao, Xiangping; Zhang, Dawei (Frontiers in Materials, 2024)
Biofilms associated bacterial infections on material surfaces have become a tremendous biomedical challenge. Developing antimicrobial coatings on biomaterial surfaces and endowing them with decent mechanical stability and biofilm inhibition capabilities is an efficient way to resist bacterial attachment and biofilm formation. Herein, we integrated 2-hydroxyethyl methacrylate (HEMA) and D-amino acid mixtures based antibiofilm combinations with sulfobetaine methacrylate (SBMA) hydrogel coatings.The obtained hydrogel coatings demonstrated high stability in various transport and service environments. The proper incorporation of the HEMA achieves only ~3% weight loss of SBMA hydrogel coatings after swelling, flushing and abrasion damages.In addition, both biofilm formation inhibiting D-amino acid mixtures and bacteriakilling gentamicin components were loaded in the coatings. The synergistic action of these two components was able to significantly reduce the bacterial numbers with up to 2.3 log reduction. The bacteria exposed to D-amino acid mixtures was difficult to form biofilm, which was more susceptive to the harm of gentamicin. This work provides an effective paradigm to integrate mechanically stable SBMA-HEMA hydrogel with natural D-amino acid mixtures based antibiofilm agents to generate biomedical surfaces to combat biofilms associated bacterial infections.